2002
DOI: 10.1093/ansci/80.8.2126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Brahman-derivative breeds and Angus on carcass traits, physical composition, and palatability1

Abstract: Steers were generated from Angus (A), Beefmaster (BM), Brangus (BA), Gelbray (GB), and Simbrah (SB) sires mated to cows of their breed and to Brahman x Hereford F1 cows (except A) to characterize their carcass traits, composition, and palatability. The 290 steers (48 A, 48 BM, 36 BA, 31 GB, and 46 SB) were slaughtered at an equal fatness end point as determined by real-time ultrasound and visual evaluation. Angus steers had lighter (P < 0.01), more youthful (P < 0.01) carcasses with a higher (P < 0.05) quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…El presente estudio detectó que GC fue influida de manera importante por la raza del animal (p<0,05), al igual que las variables R y GD (p≤0,07). Coincidiendo con estos resultados, en el estudio realizado por Bidner et al (2002), se observaron diferencias en las características de la canal en novillos descendientes de sementales de las razas Angus, Beefmaster, Brangus, Gelbray y Simbrah, los cuales fueron apareados con vacas de su misma raza y con vacas F1 Brahman×Hereford. En el estudio mencionado se encontró que los novillos hijos de toros Simbrah produjeron canales más pesadas (375 kg) comparadas con las canales de novillos hijos de toros Angus (290 kg), Beefmaster (324 kg) y Brangus (334 kg).…”
Section: Discussionunclassified
“…El presente estudio detectó que GC fue influida de manera importante por la raza del animal (p<0,05), al igual que las variables R y GD (p≤0,07). Coincidiendo con estos resultados, en el estudio realizado por Bidner et al (2002), se observaron diferencias en las características de la canal en novillos descendientes de sementales de las razas Angus, Beefmaster, Brangus, Gelbray y Simbrah, los cuales fueron apareados con vacas de su misma raza y con vacas F1 Brahman×Hereford. En el estudio mencionado se encontró que los novillos hijos de toros Simbrah produjeron canales más pesadas (375 kg) comparadas con las canales de novillos hijos de toros Angus (290 kg), Beefmaster (324 kg) y Brangus (334 kg).…”
Section: Discussionunclassified
“…However, numerous other metabolic differences also may contribute to the reduced tenderness of Bos indicus-influenced cattle (Wright et al, 2018). The use of composite breeds comprised of 3/8 or 5/8 Bos indicus inheritance is common among beef producers to incorporate the positive attributes of Bos indicus cattle, but breeds with 3/8 or 5/8 Bos indicus such as Brangus, Beefmaster and Santa Gertrudis still tend to have tougher longissimus on average than Bos taurus breeds (Crouse et al, 1989;Johnson et al, 1990;O'Connor et al, 1997;Bidner, Wyatt, Humes, Franke, & Blouin, 2002;Wheeler, Cundiff, Shackelford, & Koomaraie, 2010). For this reason, the Australian Meat Standards Australia eating quality assurance system for beef predicts lower consumer scores for any cattle with Bos Indicus content greater than 25% (Polkinghorne et al, 2008a, b).…”
Section: Breed Effectsmentioning
confidence: 99%
“…As a result of the expansion of agriculture, beef cattle production was displaced to tropical and subtropical regions, and British breeds were replaced by other genotypes, such as composites between Bos indicus and Bos taurus breeds [1]. Numerous studies have indicated that steaks from cattle of greater Bos indicus genetic influence were tougher than steaks from Bos taurus cattle [2,3]. Nevertheless, post mortem strategies such as ageing could be effective for improving tenderness [4].…”
Section: Introductionmentioning
confidence: 99%